Dual nanotransfer printing for complementary plasmonic biosensors. (11th July 2019) - Shin, Sang-Ho; Shin, Sung-Ho; Choi, Jun-Hyuk; Lee, Jihye; Choi, Dae-Geun; Jeong, Jun-Ho; Ju, Byeong-Kwon; Jung, Joo-Yun
Abstract: One of the main challenges in the widespread utilization of localized plasmon resonance-based biosensors is the fabrication of large-area and low-cost plasmonic nanostructures. In this work, we fabricated large-area and low-cost complementary plasmonic biosensors such as nanohole and nanodisk arrays using dual nanotransfer printing (NTP) with a single metal deposition and a single reusable mold. The suspended nanohole arrays and the suspended nanodisk arrays were fabricated using the subsequent dry etching process. We confirmed a maximum enhancement in bulk sensitivity in experiments and simulations by controlling the vertical and lateral etching depths of the dielectric layer underneath the gold (Au) nanohole and nanodisk arrays. Furthermore, we show that the surface sensitivity evaluated by atomic layer deposition of aluminum oxide increased because appropriate vertical and lateral etching depths allow the target analyte to access the additional near-field formed at the bottom of the Au nanostructure. The dual NTP method provides a practical solution for the realization of large-area and low-cost label-free plasmonic biosensing systems, with a reduction in complexity and cost of the fabrication process of complementary plasmonic structures and metasurfaces.